Impact of Maternal Physical Activity and Infant Feeding Practices on Infant Weight Gain and Adiposity - Lisa Chu; Ravi Retnakaran; Bernard Zinman; Anthony J. G. Hanley; Jill K. Hamilton (International Journal of Endocrinology)
Increasing evidence supports the contribution of intrauterine environmental exposures on obesity risk in offspring. Few studies have included maternal and infant lifestyle factors. Our objective was to study the impact of maternal physical activity, infant feeding, and screen time on offspring weight gain and adiposity. In a prospective cohort study, 246 mothers underwent testing during pregnancy to assess glucose tolerance status and insulin sensitivity. Anthropometry and questionnaires on physical activity, infant feeding, and screen time were completed. Multiple-linear regression was performed to examine the impact of maternal and infant factors on infant weight gain and weight-for-length z-score at 1 year. Infant weight outcomes were negatively predicted by maternal pregravid vigorous/sport index and exclusive breastfeeding duration. After adjustment, each unit increase in maternal pregravid vigorous/sport index decreased infant weight gain by 218.6 g (t=2.44, P=0.016) and weight-for-length z-score by 0.20 (t=2.17, P=0.031). Each month of exclusive breastfeeding reduced infant weight gain by 116.4 g (t=3.97, P<0.001) and weight-for-length z-score by 0.08 (t=2.59, P=0.01). Maternal pregravid physical activity and exclusive breastfeeding duration are associated with weight gain and adiposity as early as 1 year of age.